Min Je-in’s Dongmong Seunseup: Educational philosophy and modern applicability of Joseon dynasty’s first children’s character education textbook - Min, Byungchan; Min, Pilkee (Edelweiss Applied Science and Technology, 2025)
Dongmong Seunseup is a textbook authored by the Confucian scholar Min Je-in in 1543 during the mid-Joseon Dynasty period. It is the world’s first systematic textbook for children’s character education, notably produced 115 years before the writings of the Western modern educationist Comenius. The textbook integrates moral and historical instruction by grounding its curriculum in the core Confucian principles of filial piety and the five virtues (ruler–subject, father–son, husband–wife, elder–younger, and friend–friend), thereby fostering the development of morally upright individuals. This study re-examines Min Je-in’s life and educational philosophy from a contemporary perspective, providing a detailed analysis of the role Dongmong Seunseup played as an ideal model for both home and school education amid the moral confusion and political instability of its time. Furthermore, given the current decline in character education, the study shows how the educational philosophy of Dongmong Seunseup may contribute to moral restoration and stronger community consciousness, thereby presenting a modern reinterpretation and practical applicability of this traditional educational heritage. Educational policymakers and teachers should explore the contemporary applicability of Dongmong Seunseup and develop its insights into concrete educational programs.